2019
DOI: 10.26656/fr.2017.3(5).098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fermentation duration and starter concentration on physicochemical properties of modified sorghum flour by Lactobacillus plantarum FNCC 0027

Abstract: Sorghum was one of the potential crops to be developed as a food product due to its promising nutritional content. The challenges of sorghum utilization are the high amount of tannin content and its low digestibility. Processing methods such as fermentation are known to able to reduce the tannin content, increase the nutrient content and digestibility, as well as the sensory score of sorghum flour. The aim of this study was to find out the effect of fermentation duration and starter concentration of Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…However, SC gave significant effect (as compared to control) when its concentration was higher than 2%. This result is consistent with our previous study (Kurniadi et al, 2019). The effectiveness of starch degradation elevates with the increasing fermentation period and addition of SC.…”
Section: Effect Of the Fermentation Period And The Starter Culture Co...supporting
confidence: 94%
See 1 more Smart Citation
“…However, SC gave significant effect (as compared to control) when its concentration was higher than 2%. This result is consistent with our previous study (Kurniadi et al, 2019). The effectiveness of starch degradation elevates with the increasing fermentation period and addition of SC.…”
Section: Effect Of the Fermentation Period And The Starter Culture Co...supporting
confidence: 94%
“…However, the elevation of SC concentration from 2 to 6% did not significantly affect the dissolved protein content. A similar trend also occurred in our previous study using L. plantarum (Kurniadi et al, 2019). Various other fermentation studies also reported the same finding; in corn flour (Amankwah et al, 2009;Gernah et al, 2011;Aini et al, 2016); in cassava fermentation (Frediansyah et al, 2012;Gunawan et al, 2015;Frediansyah and Kurniadi, 2016); in foxtail millet fermentation (Amadou et al, 2014), and in mung bean bioprocess (Onwurafor et al, 2014).…”
Section: Effect Of the Fermentation Period And The Starter Culture Co...supporting
confidence: 87%
“…Another factor that causes a decrease in water content is the activity of microorganisms that damage the starch component thereby reducing the OH bond in its structure (Kurniadi et al, 2019).…”
Section: Uv-vis Analysis On Tempeh Dissolved Protein Contentmentioning
confidence: 99%
“…The protein content of this grain is equivalent to that of wheat (8–12%) and higher than that of rice (6–10%), while its fat content (2–6%) is higher than that of rice (0.5–1.5%). Yet, unlike other cereals, sorghum also has a testa (i.e., a dark (brown) grain coat that contains antinutritional compounds such as tannins) [ 4 ]. Tannins are polyphenolic chemicals that can form complexes with proteins and, in turn, lower protein quality and affect digestion [ 5 ].…”
Section: Introductionmentioning
confidence: 99%